Epigenetic alterations of 11beta-hydroxysteroid dehydrogenase 1 gene in the adipose tissue of patients with primary aldosteronism - Yoshimichi Takeda; Masashi Demura; Mitsuhiro Kometani; Shigehiro Karashima; Daisuke Aono; Seigo Konishi; Shin-ichi Horike; Makiko Meguro-Horike; Takashi Yoneda; Yoshiyu Takeda (Endocrine Journal)
11Beta-hydroxysteroid dehydrogenase 1 (11β-HSD1) is a key enzyme involved in metabolic syndrome. Transcript-specific epigenetic regulation of the gene encoding 11β-HSD1 (HSD11B1) has been reported. We examined the mRNA level and methylation status of the HSD11B1 promoter region in the adipose tissue of patients with primary aldosteronism (PA). We compared 10 tissue specimens from patients with PA caused by aldosterone-producing adenoma (APA) with 8 adipose tissue specimens from patients with subclinical Cushing’s syndrome (SCS) caused by cortisol-producing adenomas, 4 tissue specimens from patients with Cushing’s adenoma (Cu), or 7 tissue specimens from patients with non-functioning adrenal adenoma (NFA). PA, SCS, and Cu were diagnosed according to the guideline of the Japan Endocrine Society. The mRNA level of HSD11B1 was quantified using real-time PCR. Isolated DNA was treated with bisulfite and amplified using primers specific to the human HSD11B1 promoter region. The glycohemoglobin level was significantly higher in patients with APA, SCS, or Cu than in those with NFA (p < 0.05). Blood pressure was significantly higher in patients with APA than in those with SCS, Cu, or NFA (p < 0.01). The HSD11B1 mRNA level was significantly increased in the adipose tissues of APA or SCS patients compared with Cu or NFA patients (p < 0.05). The methylation ratio was significantly lower in SCS patients than in APA, Cu, or NFA patients (p < 0.05). HSD11B1 expression is partly controlled by an epigenetic mechanism in human tissues. The pathophysiological role of epigenetic regulation of HSD11B1 expression in adipose tissue requires further study.